2007
DOI: 10.1177/154405910708601013
|View full text |Cite
|
Sign up to set email alerts
|

Defining Subphenotypes for Oral Clefts Based on Dental Development

Abstract: Individuals with clefts present considerably more dental anomalies than do individuals without clefts. We used dental development to subphenotype clefts with the goal of identifying cleft subgroups that could have specific genetic contributions. We examined 1000 individuals, 500 with clefts and 500 without. We used several clinical features, such as cleft completeness or incompleteness, laterality, and the presence of dental anomalies to assess each individual's cleft status. We performed chi-square and Fisher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
211
4
43

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(292 citation statements)
references
References 25 publications
29
211
4
43
Order By: Relevance
“…In that context, we have shown that dental anomalies outside the cleft area could be used as additional features for the generation of more sophisticated cleft subphenotypes [Letra et al, 2007].…”
mentioning
confidence: 99%
“…In that context, we have shown that dental anomalies outside the cleft area could be used as additional features for the generation of more sophisticated cleft subphenotypes [Letra et al, 2007].…”
mentioning
confidence: 99%
“…found that dental anomalies increase with cleft severity (Stahl et al 2006;Letra et al 2007;Aizenbud et al 2011). Mutations in genes influencing both palatogenesis and dental development could also partly account for the greater prevalence of dental anomalies in individuals with clefts.…”
mentioning
confidence: 99%
“…We proposed to use dental development to subphenotype clefts. Our preliminary analysis suggests dental anomalies are preferentially associated with clefts in some families [Letra et al, 2007]. In order to extend these earlier studies, we proposed to revisit the subset of the initially genotyped families with two or more siblings affected by CL/P and perform a dental examination to broader the phenotypic description of the families.…”
Section: Introductionmentioning
confidence: 99%